Case Report: Personalized diagnosis and treatment strategies for three cases of cancer of unknown primary based on molecular testing techniques - Ding, Yao; Zhou, Kexue; Fu, Kaiwen; Liao, Xingyun; Xiong, Shuanglong; Yang, Chengxiang; Hu, Mingyang; Liang, Guanzhong; Zeng, Xianghua; Li, Yongsheng; Wang, Donglin; Li, Yan (Frontiers in Oncology, 2025)
Cancer of unknown primary (CUP) is a malignancy characterized by metastatic disease at diagnosis with an unidentified primary site, accounting for 3–5% of all cancers. Despite significant advancements in cancer diagnosis and treatment in recent years, CUP management has been challenging due to its complexity and heterogeneity; therefore, its prognosis remains poor. This report presents three cases of CUP. The first case involved a 59-year-old female whose abdominal metastatic cancer was identified to be originating from a primary cervical cancer using a 90-gene panel; the disease was controlled with targeted immunotherapy. The second case was a 56-year-old male with cervical lymph node metastatic cancer; genetic testing suggested renal cancer as the primary site, and dual-targeted therapy resulted in approximately 28% tumor reduction. The third case involved a 71-year-old female with subcutaneous metastatic cancer, which was confirmed by genetic profiling to be related to breast cancer; she achieved stable disease after chemotherapy. Diagnosis and treatment of these three CUP cases demonstrated that molecular testing could significantly improve treatment outcomes and extend patient survival. Precision medicine based on molecular detection has shown substantial value in identifying the primary site of CUP, developing personalized treatment plans, and managing the disease. However, treatment costs and patient compliance remain challenging, necessitating further research to optimize both diagnostic and therapeutic strategies.